Economic analysis of groundnut (Arachis hypogaea) and soybean (Glycine max) as intercropping plants in two agroforestry systems - KARMINI KARMINI; SRI SARMINAH; KARYATI KARYATI (Biodiversitas Journal of Biological Diversity, 2017)
Karmini, Sarminah S, Karyati. 2017. Economic analysis of groundnut (Arachis hypogaea) and soybean (Glycine max) as intercropping plants in two agroforestry systems. Biodiversitas 18: 483-493. An agroforestry is a farming system combining forestry plant and agricultural plant. Two agroforestry systems of sengon (Falcataria moluccana)-groundnut (Arachis hypogaea) and jabon (Anthocephalus cadamba)-soybean (Glycine max) have been done and are proven to be successful. The objective of this study was to analyze the application of A. hypogaea and G. max as intercropping plants in two agroforestry systems from the aspect of economy. The study was conducted from January to June 2016 in Education Forest, Forestry Faculty, Universitas Mulawarman, Samarinda City, East Kalimantan Province, Indonesia. Data analysis was done to calculate the cost, revenue, and profit of the application of A. hypogaea and G. max as intercropping plants in two agroforestry systems. The results indicate that two agroforestry systems of F. moluccana-A. hypogaea and A. cadamba-G. max are feasible and applicable to rehabilitate the critical lands. The application of A. hypogaea as an intercropping plant in the agroforestry system of F. moluccana and A. hypogaea expended total cost as much as Rp. 10,985,000.00 ha-1 cs-1, and it obtained total revenue as much as Rp. 14.000.000,00 ha-1 cs-1, so it gave profit as much as Rp. 3,015,000.00 ha-1 cs-1. An agroforestry system of F. moluccana and A. hypogaea gives many benefits from the aspect of economy, social, ecology, and conservation. Total cost, total revenue, and profit of the application of G. max as an intercropping plant in the agroforestry system of A. cadamba and G. max, in the first year in the first cropping season, were Rp. 11,019,000.00 ha-1 cs-1; Rp. 3,500,000.00 ha-1 cs-1; and Rp. 7,519,000.00 ha-1 cs-1, respectively. Although G. max farm was not profitable to do in some critical lands, the agroforestry system of A. cadamba and G. max gave many benefits from the aspect of ecology and conservation.